Peningkatan Pemeriksaan Gula Darah Melalui Pelatihan Penggunaan Point Of Care Testing Bagi Kader Kesehatan Sebagai Upaya Pencegahan Dan Pengendalian Diabetes Melitus - Trisna, Citra; Aminah, Aminah; Yuliani, RA Dewi Maria (Jurnal Pengabdian Masyarakat (Jupemas), 2026)
Diabetes mellitus is one of the non-communicable diseases with a steadily increasing prevalence worldwide, including in Indonesia. Early detection through regular blood glucose monitoring is essential to prevent complications. However, many people only check their blood sugar when symptoms appear. Therefore, it is necessary to improve the capacity of health cadres in conducting independent blood glucose examinations using Point of Care Testing (POCT). This community service program was carried out in Cukanggalih Village, Curug Bitung District, Tangerang Regency, in August 2025, involving posyandu and PKK cadres. The activities included health education, POCT training, random blood glucose testing, diabetes exercise, and evaluation through pre- test and post-test. The results showed an increase in cadres’ knowledge after the training, as indicated by the improvement in pre-test and post-test scores. Blood glucose testing of 35 participants revealed that 29 people (82.9%) were in the normal category (80–200 mg/dL), 4 people (11.4%) were high (>200 mg/dL), and 2 people (5.7%) were low (<80 mg/dL). Participants showed great enthusiasm in every activity.